KURIKULUM CINTA DALAM PENDIDIKAN ANAK: REKONSEPTUALISASI PENDIDIKAN BERBASIS WELAS ASIH, ETIKA, DAN PENGEMBANGAN KEMANUSIAAN - Nazhifatul Ulfah (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
Global education systems are increasingly confronted with processes of dehumanization driven by the dominance of instrumental rationality, market-oriented curricula, and the prioritization of cognitive efficiency over ethical and affective development. The strongest foundation for developing ethical and affective values is established in early childhood, serving as a basis for character formation that supports all learning processes and life in later adulthood. This article advances the concept of Curriculum of Love as a critical reconceptualization of curriculum theory that re-centers compassion, ethical responsibility, and human flourishing as foundational educational principles. Employing a qualitative conceptual methodology grounded in critical literature analysis, this study engages with humanistic education, moral philosophy, and contemporary curriculum discourse to interrogate the limitations of technocratic educational paradigms. The analysis reveals that the Curriculum of Love constitutes a normative–ethical framework capable of integrating cognitive, moral, and relational dimensions of learning within a holistic educational vision. By emphasizing compassionate pedagogical relationships, ethical reflexivity, and the cultivation of shared humanity, this approach challenges reductionist models of education and offers a transformative alternative for addressing global crises such as social fragmentation, intolerance, and moral disengagement. This article contributes theoretically to international curriculum studies by positioning love and compassion not as peripheral values, but as epistemological and ethical foundations of sustainable and humane education.